Sosialisasi Tentang Produk Bank Syariah Pada Siswa PPMTI Tanjung Berulak Kec. Kampar - Rifqil Khairi; Saru Reza; Hidayat Hidayat; Wahyu Febri Ramadhan Sudirman; Muhammad Zakir; Irmawanti Irmawanti (EL-EMIR INSTITUTE, 2026)
This Community Service Program (PKM) activity aims to introduce the concept of Islamic financial management to students at the Madrasah Tarbiyah Islamiah Islamic Boarding School (PPMTI) Tanjung Berulak as a solution for Islamic financial management. The method used in this research began with preparation, including coordination with the boarding school management, preparation of materials, and creation of supporting media such as presentations. On the day of the community service activity, 12th-grade students participated. The material was delivered using a lecture method, with students given material based on the theme. Following the presentation, a discussion session was held, giving students the opportunity to ask questions related to the theme, allowing them to delve deeper into the concepts taught. The results of this activity demonstrated an increased understanding of the students' understanding of the importance of Islamic financial management and their enthusiasm for applying Islamic financial principles in their daily lives. This activity is expected to not only provide direct benefits to the students but also inspire them to become agents of change in their communities, promote Islamic finance, and support the creation of a more Islamic and prosperous society.